2003
DOI: 10.17705/1cais.01114
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the Trenches of Metatriangulation Research

Abstract: In this paper we describe our application of a relatively untried research approach called metatriangulation. Metatriangulation is a three-phased, qualitative meta-analysis process that may be used to explore variations in the assumptions of alternative paradigms, gain insights into these multiple paradigms, and address emerging themes and the resulting theories. In applying this method we encountered difficulties in selecting a sample, in reaching agreement among coders, and in our attempts to build theory fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…Metatriangulation is particularly useful on topics where a rich repository of published research with contradictory, confusing, and fragmented results exists [5]. Thus, we decided to use this approach, since there are a large number of publications on digital COC, with a vast number of them having frequently inconsistent results and conflicting interpretations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metatriangulation is particularly useful on topics where a rich repository of published research with contradictory, confusing, and fragmented results exists [5]. Thus, we decided to use this approach, since there are a large number of publications on digital COC, with a vast number of them having frequently inconsistent results and conflicting interpretations.…”
Section: Methodsmentioning
confidence: 99%
“…This set of paradigm lenses appears to be suitable for our investigation since it provides a logical structure to examine and understand the changes in traditional collaboration patterns as the result of emergence of digital collaboration technology. Its value has been demonstrated in other metatriangulation reviews [5][6][7]. The three theoretical perspectives from the work of Markus and Robey [9] are briefly described in Table 1.…”
Section: Focus Paradigm Lensesmentioning
confidence: 99%
“…In the same way that traditional triangulation requires the collection of data from several different orientations, metatriangulation draws on multiple research perspectives to build a more complete understanding of a complex social phenomenon. Metatriangulation is a qualitative evaluation method that explores ‘variations in the assumptions of alternative paradigms, to gain insights into the multiple paradigms, and to address emerging themes and the resulting theories’ (Saunders et al ., , p. 5). It has been used to develop and evaluate theory and metatheory in a variety of areas including power in organizations (Jasperson et al ., ), communication and information technology (Saunders et al ., ; Adriaanse, ) and organizational geography (Del Casino et al ., ).…”
Section: Metatheoretical Evaluationmentioning
confidence: 99%
“…Metatriangulation is a qualitative evaluation method that explores ‘variations in the assumptions of alternative paradigms, to gain insights into the multiple paradigms, and to address emerging themes and the resulting theories’ (Saunders et al ., , p. 5). It has been used to develop and evaluate theory and metatheory in a variety of areas including power in organizations (Jasperson et al ., ), communication and information technology (Saunders et al ., ; Adriaanse, ) and organizational geography (Del Casino et al ., ). The method consists of three phases: Groundwork: in this phase, the research question, research domain and definitions are stated and research literature identified. Review and analysis: here, the metatheoretical lenses and their relationships are identified.…”
Section: Metatheoretical Evaluationmentioning
confidence: 99%
“…My colleagues and I used metatriangulation to try to understand power theories in the IS literature from different viewpoints. We describe our application of metatriangulation in Saunders et al [2003]. Our original intent was to consider a variety of ways of looking at power.…”
Section: Building New Theory From Reference Discipline Theorymentioning
confidence: 99%